Waiting is not easy! - Willems, Mo. (New York : Hyperion Books for Children, an imprint of Disney Book Group, 2014)
Piggie tells Gerald she has a surprise for him, but it is not there yet so Gerald must be patient.
0.9
K-3.
K-3
Keywords: Elephants -- Juvenile fiction; Patience -- Juvenile fiction; Swine -- Juvenile fiction; Elephants -- Fiction; Patience -- Fiction; Pigs -- Fiction; Elephants -- Fiction; Patience -- Fiction; Pigs -- Fiction; Humorous fiction; Readers (Publications)